Piety discourse of edmond dantes and Samsul Bahri in the count of monte Cristo and Siti Nurbaya : A Comparative Study - Shafwatullah Mushoffy (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2022)
et,1/adil,c.1